Improving Students’ skill in Writing Narrative Text Through Animation Movie - Kristiani Lisma Vera Br Ginting; Dinda Syafitri; Cahaya Riama Yanti Nehe; Nita Paskarina Manullang; Sri Ninta Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this research is to find does the animation movies can improve students’ skill and ability in writing narrative text at SMP Swasta TD Pardede Foundation at VII grade in academic year2018/2019. In this research, the researchers used classroom action research and was conducted in two cycles. Each cycles consist of four steps, there are: planning, action, observing and reflecting. This research used quantitative and qualitative research to collect the data, researchers conduct tests. The tests are pre-test and post-test.The result showed that the teaching students’ skill in writing using video can improve students’ skill in writing narrative text. An increase in mean scores indicates that there is an increase in students’ skill. The student’s pre-test score was 63.69; it increased to 72.50 in the first post-test up to 78.02 in the second post-test. From the result of the study, it can be concluded that teaching writing skill using animation videos can improve students’ writing skill. Keyword: narrative, animation movie